Losing territory: The effect of administrative splits on land use in the tropics - Marco Elías Cisneros Tersitsch; Krisztina Kis-Katos; Lennart Reiners (Asian Development Bank (ADB), 2023)
State decentralization is often promoted to improve public service delivery. However, its effects on forest conservation are ambiguous. Decentralization might not only improve local forest governance, but also change the incentives to promote agricultural expansion into forests. This study focuses on the power devolution caused by the proliferation of new administrative units in Indonesia. The discontinuous changes in government responsibilities at new administrative borders provide exogenous spatial variation to study forest outcomes. Using a spatial boundary discontinuity design with 14,000 Indonesian villages, we analyze the effects of 115 district splits between 2002 and 2014. Results show a 35% deforestation decline within new districts relative to existing districts both immediately before and after splits. In pre-split years, this can be explained through agricultural divestment by existing districts on territories that will be lost. In post-split years, the short-term forest conservation benefits seem to be rooted in temporary administrative incapacity to attract agricultural investments.
Keywords: O13; Q15; Q56; H77; 330; deforestation; decentralization; environmental protection; Indonesia; spatial RDD